Dual-wavelength Q-switched pulse generation using D-fibre and MoS2 saturable absorber - Jaddoa, M.F.; Odah, Jafer Fahdel; Ahmad, Harith; Amiri, Iraj Sadegh; Tiu, Zian Cheak (Institute of Physical Optics, 2018)
We have demonstrated a dual-wavelength Q-switched generation of erbium-doped fibre laser, which is achieved using a D-fibre and several layers of molybdenum disulfide as a saturable absorber. Bulk MoS2has been processed using a liquid-phase exfoliation to obtain a layered structure. To provide a thin-film structure, MoS2has been mixed with a polyvinyl-alcohol polymer. The dualwavelength spectrum of our device reveals two peaks centred at 1555 and 1562 nm. Q-switched operation at the both spectral peaks has been investigated using a tunable bandpass filter.